Brand creation via design and modularization: SMEs in international B2B markets - Olavi Uusitalo (jbm - Journal of Business Market Management, 2014)
Brand theory has its origins in the consumer product market and is normally considered in relation to big business. An established brand enables customers to save time by guaranteeing the level of quality, reducing purchasing risk and simplifying customer choices. Little research, however, has been carried out to investigate the relevance of brands in industrial markets, especially within small and medium enterprises (SMEs). Loyalty to a product brand can tie the customer to a supplier. In this paper, I argue that the creation of product brands via industrial design and product modularity is important for SMEs in the international business-to-business (B2B) market. To demonstrate this, I examine brand creation in three Finnish SMEs: KPatents, Modulight and Genelec. These companies have incorporated product brand creation in new product development by using industrial design and modular products. This paper contributes to research in product brand creation among SMEs in the B2B market.
urn:nbn:de:0114-jbm-v7i2.915
Keywords: 650; Brand; Industrial design; Modularity; SMEs; B2B Marketing